Oxford reading tree : level 5 : floppy's phonics : sounds and letters : . Book 28 - Hepplewhite, Debbie; Hunt, Roderick ([S.l.] : Oxford University Press, 2011)
There are 12 books at Level 5. Level 5: Book 25 'Alternative Spellings' Book 26 'Alternative Spellings' Book 27 'Alternative Spellings' Book 28 'Alternative Spellings' Book 29 'Alternative Spellings' Book 30 'Alternative Spellings' Level 5 More A: Book 31 'Alternative Spellings' Book 32 'Alternative Spellings' Book 33 'Alternative Spellings' Book 34 'Alternative Spellings' Book 35 'Alternative Spellings' Book 36 'Alternative Spellings' Each sound/alternative spelling is explored through an Oxford Reading Tree scene, first the children should read the decodable word lists, before trying to find the words within the picture. Consolidation activities include spelling activities and reading short texts. There are a total of 42 books in this series from Level 1 to Level 5 (Letters and Sounds Phase 1 to Phase 5)